2014
DOI: 10.1007/s00405-014-3449-9
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen is not a prognostic factor for response to HELP-apheresis in sudden sensorineural hearing loss (SSHL)

Abstract: Higher levels of fibrinogen or cholesterol were associated with improved hearing recovery in SSHL patients after treatment with HELP-apheresis (Heparin-induced extracorporeal LDL precipitation apheresis). The present trial was performed to demonstrate HELP-related effects on relevant metabolic and inflammatory parameters in the context of SSHL treatment. In the framework of a single arm non-controlled trial, we investigated the variation of metabolic and inflammatory parameters using HELP-apheresis for a defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The etiology of SSNHL remains unclear, and various causative factors have been proposed. 13,17,36 Patients with lowfrequency and flat-type SSNHL had larger K values and smaller angles, which indicated that they were in a relatively hypocoagulable state, as compared with those having highfrequency SSNHL and totally deafness, who were in a relatively hypercoagulable state. The reason is probably that different subgroups of SSNHL have different pathologic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The etiology of SSNHL remains unclear, and various causative factors have been proposed. 13,17,36 Patients with lowfrequency and flat-type SSNHL had larger K values and smaller angles, which indicated that they were in a relatively hypocoagulable state, as compared with those having highfrequency SSNHL and totally deafness, who were in a relatively hypercoagulable state. The reason is probably that different subgroups of SSNHL have different pathologic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low‐frequency and flat‐type SSNHL had larger K values and smaller angles, which indicated that they were in a relatively hypocoagulable state, as compared with those having high‐frequency SSNHL and totally deafness, who were in a relatively hypercoagulable state. The reason is probably that different subgroups of SSNHL have different pathologic backgrounds 13,17,36 . Nonetheless, all patients have normal coagulation function, so they should not be routinely treated with defibrinogenation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations